Integrating Digital Marketing and Maritime Branding for Cadet Recruitment in STIP Indonesia - Ratnasari, Ni Nyoman Sri; Fachruddin, Imam; Harahap, Ramadhan Hasri; Mudakir (Meteor STIP Marunda, 2025)
This qualitative study investigates the integration of digital marketing and maritime branding strategies at the Sekolah Tinggi Ilmu Pelayaran (STIP) Indonesia to enhance cadet recruitment. Through in-depth interviews, focus group discussions, and document analysis with key internal and external stakeholders, the research identifies a significant gap between the institution's official "Disciplined Guardian" brand narrative and its modern, competency-rich educational reality. Findings reveal that while the traditional brand builds trust, it under-communicates critical competencies in green shipping, technological proficiency, and seafarer wellbeing. The study concludes that STIP's marketing effectiveness can be significantly enhanced by developing a complementary "Modern Maritime Professional" archetype. This involves strategically aligning digital content with international competency frameworks (STCW, MARPOL, MLC) and formally harnessing the power of authentic, peer-generated advocacy. The research provides a practical, evidence-based framework for maritime education institutions to bridge the internal-external perception gap and more effectively attract the next generation of maritime officers.